Do Uncertainties in the Reconstruction of Land Cover Affect the Simulation of Air Temperature and Rainfall in the CORDEX Region of East Asia?. Issue 7 (1st April 2019) - Ge, Jun; Pitman, Andrew J.; Guo, Weidong; Wang, Shuyu; Fu, Congbin
Abstract: Land cover type reconstructions, required in climate models, commonly utilize remote sensing products. There are inevitable misclassifications in land cover reconstructions due to the retrieval process. We use the Weather Research and Forecasting model to determine whether these misclassifications can affect the simulations of air temperature and rainfall over the Coordinated Regional Climate Downscaling Experiment (CORDEX) East Asia region, where the accuracy of the land cover classification is low. The Moderate Resolution Imaging Spectroradiometer land cover map is used for the control simulations and is then replaced by the most likely alternative land cover type at pixels where the classification confidence is below various threshold values. Results show that misclassification‐induced land cover change can affect key biogeophysical characteristics (albedo, leaf area index, and roughness length) and these can affect the sensible and latent heat fluxes at regional scales. However, the impact on air temperature is very limited and is restricted to the Tibetan Plateau where warming of up to 2 °C occurs associated with the replacement of barren or sparsely vegetated land to grassland. The impact on rainfall is negligible, and most changes are likely caused by model internal variability rather than land cover change. Overall, uncertainties in the reconstruction of land cover have negligible impacts, and the Moderate Resolution Imaging Spectroradiometer land cover product can be used in regional simulations over East Asia. However, we note that land cover change experiments incorporating uncertainties must utilize large numbers of simulations if air temperature and rainfall changes are to be examined robustly. Key Points: Uncertainties in remotely sensed land cover have a discernible impact on the albedo, leaf area index, and roughness length Uncertainties in land cover affect the simulation of sensible and latent heat fluxes in some regions depending on how the biogeophysical characteristics change Uncertainties in land cover have negligible impacts on the simulation of air temperature and rainfall in most regions of East Asia